THE KNOWLEDGE OF GENRES OF PRIVATE JUNIOR HIGH SCHOOL TEACHERS IN MOJOKERTO (RETAIN, 2013)
THE KNOWLEDGE OF GENRES OF PRIVATE JUNIOR HIGH SCHOOL TEACHERS IN MOJOKERTO Yeviana Prameswari English Education Department, Language and Arts Faculty, Surabaya State University. Email: yeviana.prameswari@gmail.com Prof. Dr. Susanto, M.Pd. English Education Department, Language and Arts Faculty, Surabaya State University. Abstrak Berdasarkan Standar Isi untuk mata pelajaran Bahasa Inggris (BSNP,2010), ada 5 genres yang diajarkan di SMP, yang terdiri dari teks naratif, recount, deskriptif, report dan prosedure. Dalam tingkat ini, siswa harus mampu memahami berbagai macam genre. Tapi kenyataannya bahwa masih banyak siswa yang kesulitan untuk memahaminya. Untuk mengatasi masalah ini, guru menjadi orang yang paling bertanggungjawab yang mempunyai peran penting dalam proses pembelajaran. Baik guru yang menagajar di sekolah negeri dan swasta diharuskan untuk menguasai materi termasuk tentang genre. Jika guru mampu menguasai materi dengan baik, tentu itu akan membuatnya bisa mengajar dengan baik. Jadi guru harus menguasai materi pembelajaran dan keahlian mengajar dengan baik, karena kedua hal tersebut selalu berhubungan. Penelitian ini bertujuan untuk mendeskripsikan tentang kemampuan guru SMP swasta di Mojokerto tentang genre. Peneliti menggunakan metode penelitian deskriptif kualitatif. Peneliti menggunakan semi structured interview untuk mendapatkan data penelitian. Hasil dari penelitian ini menunjukkan bahwa kedua guru mampu memahami genre dengan baik. Tentunya, hasil daripenelitian ini tidak dapat mewakili seluruh guru SMP swasta di Mojokerto karena mereka mempunyai perbedaan dalam latar belakang pendidikannya. Dengan mengetahui hasil dari penelitian ini, dapat membuktikan bahwa tidak semua SMP swasta mempunyai kualitas yang buruk. Kata Kunci: Pengetahuan tentang genre, guru SMP swasta Abstract According to Standar Isi for English (BSNP, 2010), there are five genres for teaching in junior high school, they are narrative, recount, descriptive, report and procedure texts. At this level, the students have to master in comprehending various kinds of genres. But the fact is that there are some students get difficulties in comprehending genres. To overcome that kind of problem, teachers become the most responsible people who have a big duty in teaching process. Both teachers who taught in state and private junior high schools are absolutely expected to master genre in order to have deep understanding in comprehending genre. If teachers have deep understanding in comprehending genre, of course, it will make teachers become easy to teach genres to the students. So, teachers have to master teaching material and teaching skill also since both of them always interrelated. This research aims to describe the knowledge of genres of private junior high school teachers in Mojokerto. The researcher chose descriptive qualitative as the research design. The researcher conducted semi structured interview to get and complete the data. The result shows both teachers were knowledgeable in terms of understanding genres. Of course, the result of this study could not present the knowledge of genres of all private junior high school teachers in Mojokerto since they are different in background of their education. By knowing the result of this study, it proved that not all private junior high school in Mojokerto have bad quality in education. Keywords: The knowledge of genres, private junior high school teachers INTRODUCTION Text becomes a basic part in language teaching and learning, both written and spoken. According to Standar Isi for English (BSNP, 2010), there are three materials about text types for Junior high school, which are genres, speech acts, and short functional texts. Furthermore, text is considered as teaching material which cannot be separated in language teaching and learning. As Pardiyono (2007:1) states that students have to involved in the use of text types, both in the form of written and spoken text. Based on Standar Isi (BSNP, 2010), there are five genres for teaching in Junior high school, they are narrative, recount, descriptive, report and procedure texts. Besides, Pardiyono (2007: 2) states that genre as the type of text that used as the basic structure of reference so a text can be written effectively from the right purpose or grammatical pattern use. Furthermore, texts can be classified into genre according to the characteristic which includes the purpose of communication or social function, the rhetorical structure of the text or generic structure and the language features. According to what stated in Standar Isi (BSNP, 2010), genres is a teaching material which is firstly taught in Junior high school level. At this level, the students have to master in comprehending various kinds of genres. So when they graduate from Junior high school, they have good knowledge and ability in comprehending various kinds of genres and of course, it will be useful for them when they continue their study to Senior high school. As Helena (2004 : 3) states in her article that Junior high school graduates are expected to be able in comprehending the genres or participating in the creation of textwhich serves their daily needs to entertain themeselves, to carry out transactional exchanges and to write simple narratives, descriptions, reports and recounts. However the fact in school is not like what is expected. In some schools, there are many students get difficulties in comprehending genres. Not only that, they also get confused in understanding various kinds of genres. They also get confused in differentiate the various kinds of genres since each genre has its own characteristic. Besides, genres become difficult for them since they have never learned it before in Elementary school. As a result, some students got low score in their reading test which the materials are related to genres. They also got low score in writing and speaking test when their teacher asked them to write simple narratives, descriptions, reports and recounts, then presented it to the class. To overcome that kind of problem, teachers become the most responsible people who have a big duty in teaching process since they always involve in every teaching and learning process in the classroom. As Finocchiaro (1989 : 22) states that teachers are considered as one of the important key to a successful learning. To reach a successful learning, teachers must have some characteristics of a professional language teacher. Brown (2001: 430) has divided four characteristics of a professional language teacher. He states that a professional language teacher is someone who has good technical knowledge, good interpersonal skills, good pedagogical skills and good personal qualities. According to his classification, it can be concluded that a teacher who has good technical knowledge always has good understanding about teaching material. While a teacher who has good pedagogical skills, interpersonal skills and personal qualities always has better teaching skill than teacher who has not pedagogical skills, interpersonal skills and personal qualities. Furthermore, both teaching skills and teaching materials are always interrelated. To be qualified teachers they should be able to understand both of them. The teaching materials involve ‘what’ will teacher gives to the students in teaching and learning process in the classroom. While the teaching skills mean ‘how’ teacher explains the materials to the students. The previous studies about the knowledge of genres of junior and senior high school teachers conducted by Dwirasari (2011) and Rachel (2010). However, both of them have described about the knowledge of genres of state junior and senior high school teachers. Both of them chose the teacher in favourite schools which has good quality in education and almost all of the graduates have passed the national examination with good scores. In fact, some private junior high schools are underestimated by the society. In Mojokerto, some private junior high schools are selected by the students who got bad score in national examination. For the students who got good score, they never chose private junior high school. Since genres are considered as teaching material, both teachers who taught in state and private junior high schools are absolutely expected to have deep understanding in comprehending genres, they also expected to have good teaching skill to teach genres to the students. So they can explain the material about genre to the students as well as possible, then the students understand well about genre. Based on the condition, the researcher is interested to describe about the knowledge of genres of private junior high school teachers in Mojokerto. She chose two teachers who are different in gender and background of their education because of two reasons. The first reason, she found the reality in society that some of them always think that female teacher is better than male teacher. They think female teacher is more diligent, cleverer, and more attractive , so she can explain the material well. The second reason, she found the reality in society that some of them always underestimate the graduation from private university. They think that all graduation from state university are definitely have good quality and good teaching skill in education. Therefore, the researcher wanted to conduct a research which intends to describe this phenomenon, the knowledge of genres of private junior high school teachers in Mojokerto. By conducting this study, the researcher has purpose to find out the reality about the quality of the teachers who are taught in a private junior high school in Mojokerto, however they are different in gender and background of their education. By knowing the fact or the result of the study, the researcher hoped it will give meaningful contribution for junior high school teacher since it is important to measure their knowledge in order to increase their competency on mastering the teaching material includes genres. It is also expected to give meaningful contribution for school. It is important to know about teacher’s knowledge in order to guarantee that their teachers are competent in mastering the teaching material. This phenomenon makes the researcher puts her interest to conduct research about it. The researcher questions: (1) How is the ability of private junior high school teachers in Mojokerto to define genre? (2) How is the ability of private junior high school teachers in Mojokerto to mention kinds of genre? (3) How is the ability of private junior high school teachers in Mojokerto to identify each genre? (4) How is the ability of private junior high school teachers in Mojokerto to differentiate genre? METHOD Based on the research question and the objective of the study, the researcher used descriptive qualitative. Susanto (2002: 36) explained that descriptive research is a research in which the researcher has to describe and interpret the events happened in detail. In this study, the researcher described the knowledge of genres of private junior high school teachers in Mojokerto. She concentrated on two English teachers who taught in a private junior high school in Mojokerto who different in gender and background of their education. In this research, the researcher chose descriptive qualitative as the research design based on two reasons, which are the objective of this study is to describe the knowledge of private junior high school teachers about genre and there is no treatment in this study. The subjects of this study were two English teachers who are different in gender and background of their education, however they have been teaching English for the same time (7 years) in a private junior high school in Mojokerto which is underestimated by the society since this school always be the final destination for the students who got bad score in final exam and the society always think that this private junior high school has low quality in education. She chose two teachers who are different in gender and background of their education because of two reasons. The first reason, she found the reality in society that some of them always think that female teacher is better than male teacher. They think female teacher is more diligent, cleverer, and more attractive , so she can explain the material well. The second reason, she found the reality in society that some of them always underestimate the graduation from private university. They think that all graduation from state university are definitely have good quality and good teaching skill in education, however it doesn’t always guarantee. In this case, teacher A is a male who is graduated from the state university in Malang, while teacher B is a female who is graduated from private university in Jombang. Therefore, the researcher wanted to find out the knowledge of genres from both teachers. This study is taken place in the teachers’ home and office. The office is the school where the teachers work. Then the researcher conducted the first interview (related to the teachers’ knowledge to define, mention, identify and differentiate each genre) when both teacher A and B finished their duty to teach the students in the classroom, so the situation of the office was really quiet since some teachers have left the school. After conducting the first interview, both teacher A and B asked the researcher to continue the next interview in their home at Sunday morning, so the researcher came to teacher A’s home, then continued to teacher B’s home to conduct the second interview which is related to the teachers’ knowledge to differentiate five different texts given by the researcher. The consideration was made because the researcher conducted an informal interview which can be done either at school or home. The data of this study is teachers’ answer in the form of utterances and expressions given by the teachers during interview sessions which are transcribed into written form. The sources of the data are two private junior high school teachers in Mojokerto who have been teaching English in the same school for the same time (7 years), however they are different in gender and background of their education. Teacher A is a male who graduated from the state university in Malang, while teacher B is a female who graduated from private university in Jombang. The researcher interviewed the English Teacher to get the data related to their knowledge of genres. According to Susanto (2002: 22), interview is a data collection technique that uses oral questions to elicit respondents’ answer. In this study, the researcher used semi-structured interview, she set few questions as guidelines which can be added more if it is necessary. The researcher conducted the interview twice of each teacher. In the first interview, she set formal questions as the interview guideline which is related to the teachers’ knowledge to define, mention, identify and differentiate each genre, but it can be added more questions if it is necessary. Then in the second interview, She wanted to make sure about the teachers’ ability to differentiate each genre. Therefore, the researcher gave five different texts, she gave both teachers some times to read and study the texts and finally she asked them to differentiate the texts. It was done in order to complete the data and answer the last research question. In the implementation, the researcher conducted the interview informally. It was done in order to explore teachers’ knowledge and give a sense that the questions don’t sound like testing the teacher. To keep and save the data, the researcher recorded the teachers’ utterance during the interview. In this research, all the data obtained through interview were analyzed inductively in order to answer research questions stated in chapter one. The first step was accumulating the data recorded from both teachers through interview given. The first interview is related to the teachers’ knowledge to define, mention, identify and differentiate each genre, while the second interview is related to to the teachers’ knowledge to differentiate five different texts given by the researcher. After all of data accumulated, the researcher studied the data well, she described them by classifying into the finding based on the research question. In addition, all the data were collected thoroughly as happened in the reality. RESULT AND DISCUSSION This chapter presents the result and discussion of the study as the answers for the research questions: (1) How is the ability of private junior high school teachers in Mojokerto to define genre? (2) How is the ability of private junior high school teachers in Mojokerto to mention kinds of genre? (3) How is the ability of private junior high school teachers in Mojokerto to identify each genre? (4) How is the ability of private junior high school teachers in Mojokerto to differentiate genre? The Teaching of Genres in Junior High School Based on Standar Isi (BSNP, 2010), there are five genres for teaching in junior high school, they are narrative text, recount text, descriptive text, report text, and procedure text. It is a teaching material which is firstly taught in junior high school level. At this level, the students have to master in comprehending various kinds of genres. So when they graduate from junior high school, they have good knowledge and ability in comprehending various kinds of genres and of course, it will be useful for them when they continue their study to senior high school. However the fact in school is not like what is expected. In some schools, there are many students get difficulties in comprehending genres. Not only that, they also get confused in understanding various kinds of genres. They also get confused in differentiate the various kinds of genres since each genre has its own characteristic. Besides, genres become difficult for them since they have never learned it before in elementary school. As a result, some students got low score in their reading test which the materials are related to genres. They also got low score in writing and speaking test when their teacher asked them to write simple narratives, descriptions, reports and recounts, then presented it to the class. To overcome that kind of problem, teachers become the most responsible people who have a big duty in teaching process since they always involve in every teaching and learning process in the classroom. Both teachers who taught in state and private junior high schools are absolutely expected to master and have great knowledge of genres in order to have deep understanding in comprehending genres. So they can explain the material about genre to the students as well as possible and create a successful learning in the classroom. Especially for the teachers who taught in some private junior high schools which are underestimated by the society who always think that private junior high schools have bad quality in education. As teachers, they must prove to the society that it is not true. Not all private junior high schools have bad quality in education. To prove it, teachers have to master teaching material and have good teaching skill, so they can create successful learning both in state and private junior high schools. The researcher made an interview guideline to interview two English teachers who taught in a private junior high school in Mojokerto. Both of the teachers have been teaching English in the same school for the same time (7 years), however they are different in gender and background of their study. Teacher A is a male who graduated from the state university in Malang, while teacher B is a female who graduated from private university in Jombang. According to the interview done by the researcher, she could say that both teachers are knowledgeable in terms of understanding genres. So, both teachers have mastered the teaching material well to teach genres in private junior high school in Mojokerto. By knowing the fact, the teachers can prove to the society that not all private junior high schools in Mojokerto have bad quality in education. The Ability of Private Junior High School Teachers in Mojokerto to Define Genre The first research question is related to the private junior high school teachers’ ability to define genre. There were three questions based on interview guideline: (1) Based on what clearly stated in standar isi, the materials for English is about text types. Can you mention those text types? (2) Genre is one of text type. In your opinion, what is genre? (3) In English, there are four skills, which are listening, speaking, reading, and writing. In which skill do you usually teach genre? Those three questions have purpose to find out whether those teachers are able to define genre or not by knowing the position of genre as one of the text types, the definition of genre, and the skill where genre is taught. Based on the interview trancript, teacher A mentioned 3 text types which consist of genre, short functional texts and speech act. Besides, he also could mention the examples of those three text types. He said recount, procedure, narrative, descriptive, and report text are the examples of genre. While brochure and notice are the examples of short functional text. Then he said transactional and interpersonal conversation are the examples of speech act. Based on what is stated in chapter 2, genre is one of the text types which is considered as teaching material like what is stated in standar isi. In Standar Isi BSNP, there are thirteen genres considered as teaching material: narrative text, recount text, descriptive text, report text, procedure text, anecdote text, spoof text, hortatory exposition text, analytical exposition text, news item text, discussion text, review text and explanation text. Based on the interview result, the researcher concluded that teacher A knew the position of genre as one of the text types. He also mentioned the examples of genre correctly. Not only teacher A, but also teacher B could answer the question from the researcher correctly. Teacher B also mentioned that genre is considered as one of the text types. She mentioned two examples of genre correctly, which consist of recount and descriptive text. Finally, the researcher concluded that teacher B also knew the position of genre as one of the text types. For the next question, the researcher wanted to know whether the private junior high school teachers in Mojokerto could explain the definition of genre or not by giving them the second question: Genre is one of text type. In your opinion, what is genre? Based on the interview transcript, teacher A stated genre as one of the text types which has purpose. For examples, narrative text has purpose to entertain the reader, while procedure text has purpose to explain how to make or use something. He also stated that each genre has different language feature and generic structure. As written in chapter 2, genre is one of the text types which has own characters includes the social function, generic structures, and language features. Swales (1990: 58) identified a genre as a class of communicative events, the members of which share some set of communicative purposes. He also shared an essential viewpoint that all genres control a set of communicative purposes within certain social situations and that each genre has its own structural quality according to those communicative purposes. Therefore, the communicative purposes and the structural features should be identified when genres are used in writing classes. Based on the interview result, the researcher concluded teacher A knew well about the definition of genre since he gave the right definition of genre correctly by using his own words. Not only teacher A, but also teacher B could answer the question from the researcher correctly. Teacher B stated genre is a text which has general purpose. For example, recount text has purpose to retell past event in a chronological order. She also stated each of genre has each language feature and generic structure. Finally, the researcher concluded teacher B also knew well about the definition of genre since she gave the right definition of genre correctly by using her own words. It means both of them know well about the definition of genre. For the last question, the researcher wanted to know in which skill those private junior high school teachers usually teach genre by giving them the third question: In English, there are four skills, which are listening, speaking, reading, and writing. In which skill do you usually teach genre? Based on the interview transcript, teacher A stated he has taught in that school for seven years and he has taught genre in all skills. While teacher B stated genre can be taught in productive and receptive skills, so she always try to teach genre in all skills. As written in chapter 2, genre can be taught both in productive skills (speaking and writing) and receptive skills (listening and reading). Based on the interview result, the researcher concluded both teacher A and B have done the right decision by teaching genre in all skills. It is true based on what is stated in standar isi that genre can be taught both in productive and receptive skills. It means both of them knew in which skill genre can be taught. In conclusion, based on the data that the researcher gained from the interview transcript, both teacher A and B were able to define genre since they can answer those three questions correctly. They have known the position of genre as the teaching material based on what stated in standar isi, they could explain the definition of genre correctly, and they have taught genre in all skills based on what stated in standar isi that genre can be taught both in productive and receptive skills. The Ability of Private Junior High School Teachers in Mojokerto to Mention Genre The second research question is related to the private junior high school teachers’ ability to mention genre. There was a question based on the interview guideline: As you know that there are many genres. Can you mention all genres like stated in standar isi? This question has purpose to find out whether those two teachers are able to mention genre or not. In this case, the researcher wanted to know whether those two teachers are able to mention genre or not. Based on the interview transcript, teacher A stated there are thirteen genres as teaching materials. He stated recount text, narrative text, procedure text, descriptive text, report text, analytical exposition, discussion, hortatory exposition, explanation, anecdote, spoof, news item, and review are genres which are taught in senior high school. While in junior high school only five which are recount text, narrative text, procedure text, descriptive text, and report text. As stated in chapter 2 that In Standar Isi BSNP, there are thirteen genres considered as teaching material which are narrative text, recount text, descriptive text, report text, procedure text, anecdote text, spoof text, hortatory exposition text, analytical exposition text, news item text, discussion text, review text and explanation text. However there are only five genres must be taught for junior high school students which are narrative text, recount text, descriptive text, report text and procedure text. According to the data from the interview transcript above, teacher A could mention all 13 genres correctly (narrative text, recount text, descriptive text, report text, procedure text, anecdote text, spoof text, hortatory exposition text, analytical exposition text, news item text, discussion text, review text and explanation text). Furthermore he also could mention five genres for junior high school students correctly which consist of narrative text, recount text, descriptive text, report text, procedure text. Not only teacher A, but also teacher B could mention all 13 genres correctly. She stated genres which are taught in junior high school are fewer than in senior high school. In junior high school only 5 which are recount text, narrative text, report text, descriptive text and procedure text. While in senior high school are recount text, narrative text, procedure text, descriptive text, report text, analytical exposition, discussion, hortatory exposition, explanation, anecdote, spoof, news item, and review. In conclusion, based on the data that the researcher gained from the interview transcript, both teacher A and B were able to mention genre since they could answer the question correctly. The Ability of Private Junior High School Teachers in Mojokerto to Identify Genre The third research question is related to the private junior high school teachers’ knowledge of genre to identify each genre. The researcher wanted to know whether those teachers know about the communication purpose, the generic structure, and the language feature of genre or not. There are five genres for teaching in junior high school. Firstly, the researcher wanted to discuss about narrative text. She wanted to know whether those two teachers know about the communicative purpose of narrative text or not. Based on the interview transcript, teacher A stated narrative text has purpose to amuse the readers and it has conflict, however will find resolution in the end of the story. As written in chapter 2, narrative text is a kind of text which tell past story or event which shows complication and resolution. Its communicative purpose is for amusing the readers or listeners. Based on the interview result, the researcher concluded that teacher A knew well about the communicative purpose of narrative text since he could explain it by using his own words correctly. Not only teacher A, but also teacher B also knew well about the communicative purpose of narrative text. She stated that narrative text has purpose to entertain the readers, however there is conflict there. Her explanation is correct. It means both of them know about the communicative purpose of narrative text. For the next question, the researcher wanted to know whether those two teachers know about the generic structure and language feature of narrative text or not. Based on the interview transcript, teacher stated that the generic structure of narrative text consist of orientation which introduces the subject and setting, complication which tells the conflict, resolution which tells how to resolve the problem, and re-orientation which is in the form of moral value from the story. He also stated that one of the language feature of narrative text is using simple past tense. As explained in chapter 2, the generic structure of narrative text are orientation (introduces the subject and setting), complication (when the conflict is happened), resolution (resolve the problem), re-orientation (moral value from the story). While one of the language features of narrative text is Simple Past Tense. Based on the interview result, the researcher concluded that teacher A knew about the generic structure and language feature of narrative text since he could mention it correctly. Not only teacher A, but also teacher B knew about the generic structure and language feature of narrative text since she stated that the generic structure of narrative text are orientation, complication, resolution, and re-orientation. She could explain all of them by using her own words. She also stated that the language feature is simple past tense. It means both teachers A and B could mention and explain the generic structure and language feature of narrative text correctly. In conclusion, based from the result that the researcher gained from the interview transcript, the researcher can conclude that both teacher A and B were able to identify narrative text. Those can be seen from their answers when the researcher addressed some questions to them, then they could explain the communicative purpose, the generic structures and the language features of narrative text correctly. After discussing about narrative text, the researcher wanted to discuss about recount text. In this case, the researcher wanted to know whether those two teachers know about the communicative purpose of recount text or not. Based on the interview transcript, teacher A stated that recount text has purpose to retell past events and there is no complication there. As written in chapter 2, Pardiyono (2007: 94) stated that recount text is a text which retell past event chronologically and has no conflict or complication. Based on the definition of recount text above, it can be concluded that the communicative purpose or social function of recount text is to inform or to give the reader the description of what occurred and when it occurred. An example of recount text is when someone provides a chronological account of what happens in his/ her day. Based on the interview result, the researcher concluded that teacher A knew well about the communicative purpose of recount text since he could explain it correctly by using his own words. Not only teacher A, but also teacher B knew well about the communicative purpose of recount text. Based on interview transcript above, she stated that recount text has purpose to tell someone’s experience which happened in the past time. It showed us that she knew well about the communicative purpose of recount text. Finally the researcher concluded that both teacher A and B could explain about the communicative purpose of recount text correctly. Next, the researcher wanted to know whether those two teachers know about the generic structures and language features of recount text or not. Based on the interview transcript, teacher A stated that the generic structures of recount text are orientation, series of events and re-orientation. He also stated that language feature of recount text is simple past tense. Based on the interview result, the researcher concluded that teacher A knew well about the generic structure and language feature of recount text. His explanation matched with the theory in chapter 2 that the generic structures of recount text are orientation, sequence of events, and re-orientation. While one of the language features in recount text is Past Tense. Not only teacher A, but also teacher B knew about the generic structure and language feature of recount text. She also stated that the generic structure of recount text include orientation, series of events and re-orientation. She also stated that the language feature of recount text is simple past tense. Finally the researcher concluded that both teacher A and B could mention the generic structures and language features correctly, although both of them only mentioned one of the language features of recount text. In conclusion, the researcher concluded that both teacher A and B could answer all the questions correctly by explaining and mentioning the communicative purpose, generic structure, and language feature of recount text, so it means both teachers were able to identify recount text. After discussing about recount text, the researcher wanted to discuss about descriptive text. In this case, the researcher wanted to know whether those two teachers know the communicative purpose of descriptive text or not. Based on the interview transcript, teacher A stated that descriptive text has purpose to describe something, it can be thing, place or person in spesific. As written in chapter 2, the social function of descriptive text is to give description about person, place or certain thing. Depdiknas (2004: 39) states that the main purpose of descriptive text is to give information, mainly about person, place or certain thing. Based on the interview result, the researcher concluded that teacher A knew well about the communicative purpose of descriptive text since he could explain it correctly by using his own words. Not only teacher A, but also teacher B knew well about the communicative purpose of descriptive text. Based on interview transcript above, she stated that descriptive text has purpose todescribe thing, person, or place in spesific. It showed us that she knew well about the communicative purpose of descriptive text. Finally the researcher concluded that both teacher A and B could explain about the communicative purpose of descriptive text correctly. Next, the researcher wanted to know whether those two teachers know about the generic structures and language features of descriptive text or not. Based on the interview transcript, teacher A stated that the generic structures of descriptive text are identification and description. He also stated that language feature of descriptive text is present tense. From the result of interview, the researcher concluded that teacher A knew well about the generic structure and language feature of descriptive text. His explanation matched with the theory in chapter 2. According to Depdiknas (2004: 52), the generic structures of descriptive text are identification and description. Identification describes the phenomenon that we have in mind, while in description we will explain more in supporting detail in order to give clearer description, for examples about particular parts, qualities and characteristic. While one of the language features of descriptive text is present tense. Not only teacher A, but also teacher B knew about the generic structure and language feature of descriptive text. She also stated that the generic structure of descriptive text starts with identification which is for explaining something which will be described in the next paragraph, then continued with description which explain something in identification in detail. She also stated that the language feature of descriptive text is present tense. Finally the researcher concluded that both teacher A and B could mention the generic structures and language features of descriptive text correctly, although both of them only mentioned one of the language features of descriptive text. In conclusion the researcher concluded that both teacher A and B could answer all the questions correctly. It means both teachers were able to identify descriptive text since they could mention and explain the communicative purpose, generic structure and language featureof descriptive text correctly. After discussing about descriptive text, the researcher wanted to discuss about report text. In this case, the researcher wanted to know whether those two teachers know the communicative purpose of report text or not. Based on the interview transcript, teacher A stated that report text has purpose to describe something in general, it can be thing, place or person. Agustien (2004) stated that report text has function to give information about something or fact in reality as a result of research or analysis. The description in report text is in the form of general conclusion. Based on the interview result, the researcher concluded that teacher A knew well about the communicative purpose of report text since he could explain it correctly by using his own words. Not only teacher A, but also teacher B knew well about the communicative purpose of report text. Based on interview transcript above, she stated that report text has purpose to describe thing, person, or place in general. It showed us that she knew well about the communicative purpose of report text. Finally the researcher concluded that both teacher A and B could explain about the communicative purpose of report text correctly. Next the researcher wanted to know whether those two teachers know about the generic structure and language feature of report text or not. Based on the interview transcript, teacher A stated that the generic structures of report text are general classification and description. He also stated that language feature of report text is present tense. Based on the interview result, the researcher concluded that teacher A knew well about the generic structure and language feature of report text. His explanation matched with the theory in chapter 2. Anderson and Anderson (2003) explain about the generic structure of Report Text, those are: a general opening statement, a series of paragraph about the subject, and a concluding paragraph. While one of the language features of report text is present tense. Not only teacher A, but also teacher B knew about the generic structure and language feature of report text. She also stated that the generic structure of report text starts with general description and then description. While the language feature use present tense. Finally the researcher concluded that both teacher A and B could mention the generic structures and language features of report text correctly, although both of them only mentioned one of the language features of report text. In conclusion, the researcher concluded that both teacher A and B could answer all the questions correctly. It means those two teachers were able to identify report text since they could mention and explain the communicative purpose, generic structure and language feature of report text correctly. After discussing about report text, the researcher wanted to discuss about procedure text. In this case, the researcher wanted to know whether those two teachers know the communicative purpose of procedure text or not. Based on the interview transcript, teacher A stated that procedure text has purpose to explain how to use or make something. As stated in chapter 2, a procedure text is a piece of text that tells people to do something. It is aimed to provide instructions for making something, doing something or getting somewhere (Anderson and Anderson, 2003: 50). In this case, procedure text can be in many kinds of forms, such as instructions, guidance, rules, recipes, etc. Based on the interview result, the researcher concluded that teacher A knew well about the communicative purpose of procedure text since he could explain it correctly by using his own words. Not only teacher A, but also teacher B knew well about the communicative purpose of procedure text. Based on interview transcript above, she stated that procedure text has purpose to explain the steps or gives information to the readers how to make or use something. It showed us that she knew well about the communicative purpose of procedure text. Finally the researcher concluded that both teacher A and B could explain about the communicative purpose of procedure text correctly. Next the researcher also wanted to know whether those two teachers know about the generic structure and language feature of procedure text or not. Based on the interview transcript, teacher A stated that the generic structures of procedure text are goal, materials, and steps. He also stated that language feature of procedure text uses imperative sentences. Based on the interview result, the researcher concluded that teacher A knew well about the generic structure and language feature of procedure text. His explanation matched with the theory in chapter 2. Anderson and Anderson (2003) explain the generic structure of procedure text, those are an introductory statement giving the aim or goal, materials needed for completing the procedure, and a sequence of steps in the correct order. Not only teacher A, but also teacher B knew about the generic structure and language feature of procedure text. She also stated that the generic structure of procedure text starts with goal, then materials, then the steps. While the language feature uses command and imperative sentences. Finally the researcher concluded that both teacher A and B could mention the generic structures and language features of procedure text correctly, although teacher A only mentioned one of the language features of procedure text. In conclusion, the researcher concluded that both teacher A and B could answer all the questions correctly. It means both teachers were able to identify procedure text since they could explain the communicative purpose, generic structure and language feature of procedure text correctly. The Ability of Private Junior High School Teachers in Mojokerto to Differentiate Genre The last research question is related to the teachers’ knowledge to differentiate genre. In this case, the researcher wanted to know whether those two teachers are able to differentiate genre or not by conducting interview twice. In the first interview, the researcher gave a question : Based on the characteristic of the text, there are some genres have almost the same characteristic, for example narrative and recount text, report and descriptive text. How do you usually differentiate them? Then in the second interview, the researcher wanted to make sure about the teachers’ ability to differentiate each genre. Therefore, she gave five different texts to both teacher A and B. After she gave five different texts, then she gave both teachers some times to read and study the texts and finally she asked them to differentiate the texts. It was done in order to complete the data and answer the last research question. From the interview transcript, both teacher A and B explained the way they differentiate genre clearly by using their own examples. Teacher A stated there are five genres which are taught in junior high school. He also stated there are some genres which have the similar communicative purpose, they are narrative and recount text, then descriptive and report text. He explained that narrative and recount text tell about the past events and use simple past tense, however there is a conflict in narrative text and there is no conflict in recount text and only tell the sequence of events. He also stated that descriptive and report text have purpose to describe something, it can be person, place or thing. However descriptive text is a text which describes something in spesific, but report text describes something in general. He explained more his answer by giving examples : if the student wants to describe “Pet” , that is report text since there are many kinds of pet that can be described. But if the student wants to describe “My Pet”, that is descriptive text since the description is spesific, it is limited with only the student’s pet. Based on the interview result, the researcher concluded that teacher A could explain the point which made each genre different from another, although some of them have similar communicative purpose. His explanation matched with the theory in chapter 2 that there is a conflict in narrative and there is no conflict in recount text. Besides, descriptive text and report text have purpose to describe something, however descriptive text describes something in spesific, while report text describes something in general. Not only teacher A, but also teacher B could explain the point which made each genre different from another, although some of them have similar communicative purpose. She stated that the genres which have the similar communicative purpose and generic structure are descriptive and report text, then narrative and recount text. She stated that descriptive text describes something in spesific, so it is limited with the writer’s hobby. However report text is more general. Then narrative text is similar with recount text which tell past events, however there is conflict in narrative text. Finally, the researcher concluded that both teachers have already known the point which differentiate each genre. Next the researcher conducted the second interview by giving five different texts, then asked both teachers to differentiate them and explained the reason. From the interview transcript, teacher A stated that text 5 is narrative text since there is complication in paragraph 2, while text 2 is recount text since it is no complication and it just tells the series of events. Then text 4 is descriptive text since the writer describes the animal in spesific. Text 1 is report text since the writer gives information in general. And for the last, text 3 is procedure text since there are goal, materials, and steps. From the result of second interview, the researcher concluded that teacher A answered correctly based on the key answer that made by the researcher. Not only teacher A, but also teacher B also answered correctly based on the key answer that made by the researcher. Teacher B stated text 5 is narrative text since there is complication. Then text 2 is recount text since there is no conflict. Text 4 is descriptive text since it describes something in spesific. Text 1 is report text since it describes something in general. Text 3 is procedure text since it gives information how to make something Finally, the researcher knew that both teacher A and B stated that text 1 is report text, text 2 is recount text, text 3 is procedure text, text 4 is descriptive text, and text 5 is narrative text. They also could explain the reason correctly. It means both teachers could differentiate all texts given into the right genre. In conclusion, the researcher concluded that both teacher A and B were able to differentiate genre since they have already known the points which differentiate each genre and could differentiate all texts given into the right genre. CONCLUSION AND SUGGESTION Conclusion The main problem of this study is the private junior high school teachers’ knowledge about genres. The main problem that is developed based on the teachers’ knowledge of genres divided into four, they are: (1) The ability of private junior high school teachers in Mojokerto to define genre, (2) The ability of private junior high school teachers in Mojokerto to mention kinds of genres, (3) The ability of private junior high school teachers in Mojokerto to identify each genre, (4) The ability of private junior high school teachers in Mojokerto to differentiate genre. Based on the finding of data analysis and discussion in previous chapter, the researcher drew a conclusion: First, both teacher A and B were able to define genre since they could answer those three questions correctly. They have known the position of genre as the teaching material based on what stated in standar isi, they could explain the definition of genre correctly, and they have taught genre in all skills based on what stated in standar isi that genre can be taught both in productive and receptive skills. Second, both teacher A and B were able to mention genre since they could answer the question correctly. Third, both teacher A and B were able to identify each genre (narrative, recount, descriptive, report and procedure text). They could explain the right communicative purpose of each genre, besides they knew exactly the generic structure of each genre and they also could mention the language feature of each genre correctly. Fourth, both teacher A and B were able to differentiate genre since they have already known the points which differentiate each genre and could differentiate all texts given into the right genre. In conclusion, both teacher A and B were knowledgeable in terms of understanding genres. So, both teachers have mastered the teaching material well to teach genres in private junior high school in Mojokerto. By knowing the fact, the teachers can prove to the society that not all private junior high schools in Mojokerto have bad quality in education. Suggestions The result of this study was that the teachers were knowledgeable in terms of understanding genres as teaching material. In this case, the researcher suggests to teachers to improve their teaching skill also since the teaching skill and teaching material are interrelated. Besides, the researcher suggests to other researchers to conduct a similar study, but they can view from other subject, for example teachers who have low and high GPA. REFERENCES Anderson, Mark and Kathy Anderson. 2003. Text Types in English 1. Sidney: Mac Millan Education Australia Pty Ltd. Anderson, Mark and Kathy Anderson. 2003. Text Types in English 2. Sidney: Mac Millan Education Australia Pty Ltd. Anderson, Mark and Kathy Anderson. 2003. Text Types in English 3. Sidney: Mac Millan Education Australia Pty Ltd. Agustien, Helena I. R. 2004. The English Curriculum in a Nutshell (paper) Presented at National Seminar. The Teaching of ESL in Indonesia; A Reflection. 2 Oktober 2004, Malang. Brown, H. Douglas. 2001. Teaching by principles: an interactive approach to language pedagogy. New York: Addison Wesley Longman, Inc. Bsnp_Indonesia. 2010. Standar Isi. Retrieved from http: // www.bsnp_indonesia.org.id retrieved at March 21st 2011 Darewianka, Baverly. 1995. Exploring How Texts Work. Newton: Primary English Teaching Association. Departemen Pendidikan Nasional. 2004. Standar Kompetensi Mata Pelajaran Bahasa Inggris SMP dan MTs. Jakarta: Depdiknas. Emilia, Hermawan, B. and Tati, D. 2008. Pendekatan Genre Based dalam kurikulum Bahasa Inggris Tahun 2006: Penelitian Tindakan Kelas di sebuah SMP Negeri di Bandung. Retrieved from http:// www.inggris.sps.upi.edu at March 21st 2011. Finocchiaro, Mary. 1989. Some facts about language teaching in the elementary school: teaching children foreign language. New York: Mc Graw- Hill book company. Nunan, David. 1992. Research Method in Language Learning. Cambridge: Cambridge University Press. O’ Conner, J. 2005. Literacy in context for GCSE. Cambridge: Cambridge University Press. Pardiyono. 2007. Pasti Bisa!! Teaching Genre- Based Writing. Yogyakarta: CV. Andi offset. Susanto. 2002. Develpoing a research proposal (a Practical Guideline). Universitas Negeri Surabaya. Susarno, Lamijan H., et al. 2007. Refleksi Pendidikan Masa Kini. Surabaya: Universitas Negeri Surabaya Swales, J.M. 1990.Genre analysis: English in academic and research. Cambridge: Cambridge University Press